Evaluating the knowledge of stroke management among the non-neurological healthcare professionals in an underdeveloped county in Southwestern China - Xia Huang; Yuanbin Zhao; Shiquan Wang; Chao Lin; Li Xie; Ping Li; Xilin Liu; Zihan He; Lili Yang (PLoS ONE, 2026)
Objective This study aims to investigate the knowledge of stroke management among non-neurological healthcare professionals (HCPs) in an underdeveloped county in western China. Methods The study proceeded in two phases. First, the Acute Stroke Management Questionnaire (ASMaQ) underwent a systematic intercultural adaptation into Chinese, followed by an evaluation of its psychometric properties. Second, a cross‑sectional survey using the adapted Chinese ASMaQ was administered to non‑neurological HCPs working in an underdeveloped county in southwestern China. A convenience sampling method was used in the recruitment. Demographic information, including age, gender, years of service, job position (doctor/nurse), department, professional level, medical facility level (comprehensive hospital/noncomprehensive medical facility), and whether the participant had a neurologist partner or not during routine practice, was collected. The internal consistency was then measured with Cronbach’s α. Further statistical analyses were conducted to identify potential influencing factors of the ASMaQ score. Results After a standardized intercultural adaptation and evaluation process, a reliable localized Chinese version of ASMaQ was obtained, with an overall Cronbach’s α value of 0.77. A total of 252 HCPs completed the questionnaires, and 225 qualified questionnaires were included in the statistical analysis. The results revealed that the rate of good performance of overall ASMaQ among non-neurological HCPs was 69.4%. For the three subscales of ASMaQ, the rates of good performance for general stroke knowledge (GSK), hyperacute stroke management (HSM), and advanced stroke management (ASM) were 73.3%, 64.7%, and 70.1%, respectively. Furthermore, we found that the factors influencing the overall ASMaQ score were primarily gender, job position, medical facility level, and with/without neurologist partners. Specifically, females performed worse than males did (106.7 ± 7.7 vs. 110 ± 8.1; P = 0.003), nurses performed worse than doctors did (106.3 ± 7.6 vs. 110.0 ± 7.9; P < 0.001), the HCPs in noncomprehensive medical facilities performed worse than those in comprehensive hospitals did (105.2 ± 9.3 vs. 108.5 ± 7.3; P = 0.02), and the HCPs without neurologist partner in the routine clinical practise performed worse than those with (106.1 ± 8.1 vs 109 ± 7.5, P = 0.005). Multiple regression analysis revealed that the job position and the level of medical facility were the independent influencing factors for the total ASMaQ score (P < 0.001). Conclusion The Chinese version of ASMaQ comprehensively assesses the understanding of stroke management knowledge among HCPs. This study reflected the lack of stroke management knowledge among non-neurological HCPs in underdeveloped western regions of China for the first time and revealed that nurses and HCPs in noncomprehensive medical facilities were more likely to have insufficient knowledge of stroke management. Strengthening their training will significantly help improve stroke treatment rates, thereby reducing the burden of stroke-related morbidity and mortality.